2021
DOI: 10.3390/ani11123513
|View full text |Cite
|
Sign up to set email alerts
|

Productive Performance, Ovarian Follicular Development, Lipid Peroxidation, Antioxidative Status, and Egg Quality in Laying Hens Fed Diets Supplemented with Salvia officinalis and Origanum majorana Powder Levels

Abstract: This study aimed to assess the effect of dietary supplementation with different levels of Salvia officinalis and/or Origanum majorana on productive performance, ovarian follicular development, lipid peroxidation, antioxidative status, and egg quality in laying hens. Two hundred and ninety-four 45-week-old Bovans brown hens were allocated into seven groups, with seven replicates of six hens each. The first group was fed with the basal considered as a control (A); the second (B) and third (C) groups were provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
1
11
1
Order By: Relevance
“…Cholesterol levels are important for laying hens as it provides the backbone for sex hormones, which is crucial during the laying phase (Naber, 1976). However, our study and previous studies are inconsistent on the impact of EOO on cholesterol levels in laying hens (Bozkurt et al, 2016;Gul et al, 2019;Migliorini et al, 2019;Saleh et al, 2021). Differences in cholesterol levels between our study and previous studies may be due to different inclusion rates of the essential oil, feeding schedule, or preparation method of the essential oil (Lim et al, 2006).…”
Section: Blood Lipid Profilecontrasting
confidence: 75%
See 2 more Smart Citations
“…Cholesterol levels are important for laying hens as it provides the backbone for sex hormones, which is crucial during the laying phase (Naber, 1976). However, our study and previous studies are inconsistent on the impact of EOO on cholesterol levels in laying hens (Bozkurt et al, 2016;Gul et al, 2019;Migliorini et al, 2019;Saleh et al, 2021). Differences in cholesterol levels between our study and previous studies may be due to different inclusion rates of the essential oil, feeding schedule, or preparation method of the essential oil (Lim et al, 2006).…”
Section: Blood Lipid Profilecontrasting
confidence: 75%
“…Plasma triglycerides were significantly lower in birds supplemented with EOO. One explanation could be interrupting the mechanisms involved in lipogenesis as described by Saleh et al (2021) who supplemented laying hens with dietary oregano and sage oil. Another possible explanation could be the influence of essential oils on inhibiting enzymes utilized in the process of lipogenesis as described by Dehghani et al, 2019 who supplemented dietary thyme essential oil to quail.…”
Section: Blood Lipid Profilementioning
confidence: 99%
See 1 more Smart Citation
“…[ 27 ] reported that the average weight of Pengging duck egg was 63.66 g at a feed consumption of 160 g. The ducks used in their study were old or pre-molting; for this reason, their production performance was low. In old age, the ovarium and oviduct weight decreases [ 28 ], the levels of hormones required for the process of egg formation decrease, and egg production becomes low [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The broiler response to diets supplemented with prebiotics, probiotics, or herbal mixtures ( Origanum majorana , Carum carvi , and Foeniculum vulgare ) as alternatives to antibiotics indicated that the herbal mixture group recorded the highest productive performance [ 14 ]. Moreover, Saleh et al [ 15 ] added a mixture of OM and another medicinal herbal plant to laying hen diets and noticed an improvement in their productivity and performance, including the feed conversion ratio and egg quality and quantity.…”
Section: Introductionmentioning
confidence: 99%